Progress in molecular biology and translational science. - Teplow, David B. (Progress in molecular biology and translational science, 2018)
'Progress in Molecular Biology and Translational Science' provides in-depth reviews on topics of exceptional scientific importance. Each volume is edited by an internationally recognized expert who selects contributors at the forefront of each field.